2022
DOI: 10.3389/fped.2021.773188
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of aEEG During Sleep and Wakefulness in Healthy Children

Abstract: IntroductionInterpretation of amplitude-integrated EEG (aEEG) is hindered by lacking knowledge on physiological background patterns in children. The aim of this study was to find out whether aEEG differs between wakefulness and sleep in children.MethodsForty continuous full-channel EEGs (cEEG) recorded during the afternoon and overnight in patients <18 years of age without pathologies or only solitary interictal epileptiform discharges were converted into aEEGs. Upper and lower amplitudes of the C3–C4, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…The absence of sleep-wake cycles coheres with brain lesions, cerebral hemorrhages, higher CRIB scores and mortality rates in preterm infants ( 27 , 28 ). A correlation between sleep-wake cycles and neurodevelopmental outcome has been shown previously ( 29 , 30 ). We found higher numbers of sleep-wake cycles in the paracetamol group as compared to the control group in the first 4 weeks of life in the overall cohort, and in the first 3 weeks of life in the subgroup of extremely preterm infants.…”
Section: Discussionsupporting
confidence: 71%
“…The absence of sleep-wake cycles coheres with brain lesions, cerebral hemorrhages, higher CRIB scores and mortality rates in preterm infants ( 27 , 28 ). A correlation between sleep-wake cycles and neurodevelopmental outcome has been shown previously ( 29 , 30 ). We found higher numbers of sleep-wake cycles in the paracetamol group as compared to the control group in the first 4 weeks of life in the overall cohort, and in the first 3 weeks of life in the subgroup of extremely preterm infants.…”
Section: Discussionsupporting
confidence: 71%
“…Many children undergoing aEEG monitoring in the PICU receive sedatives, suffer from intracranial pathologies or fall asleep during part of the recording. We previously showed that amplitudes differ between deep and light sleep in healthy children (13, 29), making the establishment of reference values during sleep substantially more difficult. For this reason, we focused on awake aEEGs as a first step toward a systematic aEEG assessment.…”
Section: Discussionmentioning
confidence: 99%
“…aEEG has proven useful for the assessment of seizures and guiding antiepileptic treatment in critically ill children (3)(4)(5)(6)(7). There is incipient but growing evidence that physiological and pathological conditions induce changes in the background pattern, e.g., sleep states, sedation, cardiac arrest, central nervous system infections, and inflammation (4,5,(8)(9)(10)(11)(12)(13). Normalization of background patterns according to a neonatal classification (14) has been described to be predictive of outcome in neonates, children, and adults after hypoxic events (9,(15)(16)(17).…”
mentioning
confidence: 99%
“…SG and NB measured the upper and lower amplitude borders manually with the integrated tool for amplitude measurement as previously described ( 13 ) ( Figure 1B ).…”
Section: Methodsmentioning
confidence: 99%
“…As an alternative, aEEG has proven useful for the assessment of seizures and guiding antiepileptic treatment in critically ill children, making it the preferred tool by pediatric intensive care givers ( 1 , 3 7 ). There is incipient but growing evidence that physiological and pathological conditions induce changes in the aEEG background pattern, e.g., sleep states, sedation, cardiac arrest, central nervous system infections, and inflammation ( 4 , 5 , 8 13 ). Normalization of background patterns according to a neonatal classification ( 14 ) is associated with outcome in neonates, children, and adults after hypoxic events ( 9 , 15 17 ).…”
Section: Introductionmentioning
confidence: 99%